The practical protection of taxpayers' rights in Mauritius: a legal analysis of the application of the minimum standards established by the international fiscal association in its general report in 2015 - Phul, Ahmad Khalid (Department of Commercial Law, 2022)
The effective protection of taxpayers' rights has not kept pace with the ongoing internationalisation of tax laws. The International Fiscal Association sought to clear this gap by drawing from the experiences of various countries on the subject. This endeavour culminated into a report in 2015 outlining 57 minimum standards for the practical protection of taxpayers' fundamental rights. The report is based on an analytical framework in the form of tax relationships, as well as on a normative framework, which acknowledges that taxpayers have fundamental rights and are protected by certain legal principles. This dissertation will analyse the application of the minimum standards in Mauritius by adopting the frameworks used in the report to provide insight into areas of tax relationships which are vulnerable whilst highlighting fundamental rights and legal principles which require urgent protection.